Pengaruh Desain Pembelajaran berbasis Nature of Science terhadap Pemahaman Siswa Sekolah Dasar - Yudi Yanuar; Ari Widodo (Universitas Kanjuruhan Malang, 2021)
The purpose of this study was to determine the effect of Nature of Science (NoS) -based learning design on elementary school students' understanding. The research method used a quantitative approach with pre-experimental design types of pre-test and post-test one group design and the sampling technique used was purposive sampling. The sample of the study was 28 students of grade VI, one of the elementary schools in the city of Bandung with learning materials about the earth and the universe. The data collection technique used a questionnaire with 24 questions using a linkert scale. The results showed that the NoS-based learning design was able to improve the understanding of elementary school students even though it was not too significant. The highest increased understanding was on the subjective aspect, while the lowest increased understanding was on the empiric based aspect. So it can be said that there is an effect of NoS-based learning design on student understanding, because this learning design is designed to make it easier for teachers and students to understand NoS.